Introducing a basic psychological performance demand model for sport and organisations. Issue 2 (3rd July 2019) - Hudson, J.; Males, J. R.; Kerr, J. H.
ABSTRACT: This study presents the development of a basic psychological performance demand model (PDM) for sport and organisations, adopting a process view of performance underpinned by reversal theory (Apter [2001] An introduction to reversal theory. In M. J. Apter (Ed.), Motivational styles in everyday life: A guide to reversal theory (pp. 3-36⁠). Washington, DC: American Psychological Association). Six elite coaches with extensive coaching experience at European, Commonwealth, Olympic and Paralympic Games were interviewed. Their interview statements were analysed using a combination of deductive and inductive analysis procedures for qualitative data. In conjunction with the interviewer, coaches developed PDMs for their specific sports. Analysis of interview data and coaches' specific PDMs identified four main cross-sport themes or fundamental psychological capabilities required for meeting performance demands. These were: Mastery motivation, Decision making, Execution, and Teamship. The PDM offers a starting framework for a new basic performance model that is novel and pragmatic with potential applicability across sports and organisations. The model is useful in its existing form, but needs further testing, extended practical application and reflection by coaches, athletes, and sport psychologists. It has potential for use in other coaching contexts beyond sport, such as business, leadership development, education, and health.